2014
DOI: 10.1007/s13199-014-0291-1
|View full text |Cite
|
Sign up to set email alerts
|

The diversity of endophytic fungi in the above-ground tissue of two Lycopodium species in Poland

Abstract: Endophytes are a large and diverse group of fungi that colonize healthy plant tissues without causing any symptoms. The majority of studies have focused on angiosperm and conifer hosts and few have examined the endophytes of lycophytes. In the present study, we characterized culturable endophytic fungi in two closely related Lycopodium species (L. annotinum and L. clavatum) from pine, beech, oak and spruce forests across Poland. More than 400 strains were isolated but only 18 Ascomycete species were identified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 67 publications
2
8
0
Order By: Relevance
“…Several studies have shown the detection and isolation of pathogenic fungi in endophytic communities of diverse host plants ( Sun et al, 2012 ; Wearn et al, 2012 ). This confirm the observation of Pawłowska et al (2014) which suggested that endophytism is a period in the life cycle of pathogenic microorganisms ( Schulz and Boyle, 2005 ).…”
Section: Discussionsupporting
confidence: 89%
“…Several studies have shown the detection and isolation of pathogenic fungi in endophytic communities of diverse host plants ( Sun et al, 2012 ; Wearn et al, 2012 ). This confirm the observation of Pawłowska et al (2014) which suggested that endophytism is a period in the life cycle of pathogenic microorganisms ( Schulz and Boyle, 2005 ).…”
Section: Discussionsupporting
confidence: 89%
“…We therefore agree with Pawłowska et al. (), who suggested that the roles of endophytic fungi and bacteria in interactions are still unknown.…”
Section: Discussionsupporting
confidence: 93%
“…[45], Lycopodium annotinum L., and Lycopodium clavatum L. [46], blackcurrant berries of Lithuania [28], and Jingbai pear of China [30]. The majority of the class were found to be endophytes, saprobes growing on woody debris, decaying leaves or dung, as well as several plant pathogens [20,46,47]. Sordariomycetes were most abundant in flowers, and have the greatest impact on the mycobiota structure of flowers.…”
Section: Discussionmentioning
confidence: 99%